Increasing Efficiency in Public Administration Through a Better System of Administrative Justice - Batalli, Mirlinda; Pepaj, Islam (Pécs journal of international and European law, 2018)
This article seeks to examine the role of administrative justice in increasing the efficiency in public administration. The article intends to analyze the connection between the capacity of judicial review of administrative acts as a crucial instrument to improve the functioning and efficiency of the administration and to ensure good governance in general. The article raises the question how the judicial review of administrative decisions affects the level of efficiency in public administration through increasing the legal security, prevention of arbitrariness and raising public confidence? There is a causal relation between administrative justice and the level of efficiency of public administration, therefore the system of judicial review should be considered as the main mechanism to promote the main principles of good governance toward more efficient, transparent and accountable decision making process.